TP8.2.3 Horses for Courses – the Impact of Covid-19 on Surgical Training Courses. (28th October 2021) - Ali, Roshneen; Baker, Alexander; Lewis, Christopher
Abstract: Aims: Surgical training has been disrupted by the Covid-19 pandemic. Educational courses may be mandatory for training progression, complementing critical skills for surgical trainees. Previous work collated a first comprehensive database of available courses. The aim of this project was to determine the extent of disruption caused to courses by the current pandemic. Methods: A snowballing approach was used to systematically search all online resources for courses available in 2021. This included websites of the Royal Colleges, sub-speciality societies, trainee organisations, regional centres, deaneries and surgical technology companies. Course target grade, price, provider and dates were collated and compared to matching data from 2020. Results: 35 sources yielded 127 courses. Since 2020, 78 courses had been cancelled and 37 new courses had been introduced. Courses price ranged between £90-1260 (median £495), with 12 courses increasing in cost overall and 4 reducing in cost due to online delivery. Only 13/127 courses were delivered online, 9 of which were newly available in 2021. Technical, clinical and revision courses constituted the majority (115/127), with only 3 courses dedicated to leadership or research. Conclusions: Educational courses supplement aspects of deanery-led teaching which are perceived to be lacking. However, course providers must respond to the need of trainees and adapt to the training restrictions necessitated by the Covid-19 pandemic by improving the availability of online courses. Whilst technical skills are often the primary focus of surgical training, the importance of non-technical, leadership and research skills is arguably greater than ever and should be recognised.